Micro-mechanism elucidation of the effects of dehydration on waterlogged historic silk (Bombyx mori) by near-infrared spectroscopy. (September 2015) - Gong, Decai; Zhu, Zhanyun; Liu, Liu
<x content-type="archive" xml:space="preserve">Abstract</x> It is widely accepted experience among archaeologists that the mechanical properties of waterlogged historic silk artifacts will be improved to some extent after the gradual evaporation of water. For the purpose of understanding the micro-mechanism of this interesting phenomenon, near-infrared spectroscopy was applied to study the microstructure of historic silk fibers before and after the transition from a water-saturated to dry state. It is demonstrated that the interaction of water with silk varies significantly depending on the condition of the material. The change of moisture content can induce rearrangement of hydrogen bonds and conformation transition in silk fibers, thus altering their mechanical properties. Our results vindicate the practical observation that by exploiting the dehydration effects, fragile water-saturated silk artifacts in archaeological sites can successfully be extracted and transported to conservation laboratories with reduced risk of damage.